A comprehensive review of primary strategies for tar removal in biomass gasification. (15th January 2023) - Cortazar, M.; Santamaria, L.; Lopez, G.; Alvarez, J.; Zhang, L.; Wang, R.; Bi, X.; Olazar, M.
Highlights: Primary strategies for removing tar were assessed. Tar formation represents the major challenge of biomass gasification. Tar concentration depends on biomass nature, process conditions and reactor design. Primary methods may not be efficient enough to completely remove tar. Reactor design plays a critical role on tar conversion and gasification efficiency. Abstract: In the current energy scenario, the production of heat, power and biofuels from biomass has become of major interest. Amongst diverse thermochemical routes, gasification has stood out as a key technology for the large-scale application of biomass. However, the development of biomass gasification is subjected to the efficient conversion of the biochar and the mitigation of troublesome by-products, such as tar. Syngas with high tar content can cause pipeline fouling, downstream corrosion, catalyst deactivation, as well as adverse impact on health and environment, which obstruct the commercialization of biomass gasification technologies. Since the reduction of tar formation is a key challenge in biomass gasification, a comprehensive overview is provided on the following aspects, which particularly include the definition and complementary classifications of tar, as well as possible tar formation and transformation mechanisms. Moreover, the adverse effects of tar on downstream applications, human health or environment, and tar analyzing techniques (online and off-line) are discussed. Finally, the primary tar removal strategies are summarized. In this respect, the effect of key operation parameters (temperature, ER and S/B), catalysts utilization (natural and supported metal catalysts) and the improvement of reactor design on tar formation and elimination was thoroughly analyzed.